Assessing green space indicators: A case study of Sarajevo, Bosnia and Herzegovina - Dženana Tatlić; Azra Čabaravdić; Muhamed Bajrić; Melisa Ljuša; Sanela Klarić; Emira Hukić
The main objectives of this study were to 1) assess the following quantitative urban green space (UGS) indicators: share of UGS, total UGS per capita, and the public UGS per capita for Sarajevo and its corresponding municipalities; 2) propose the minimum area of UGS per capita and the minimum functional UGS area per capita; and 3) discuss the methodological approach used and its applicability and relevance for UGS quantity and quality assessment. UGSs were photo-interpreted based on orthophotos and Google Satellite images and mapped manually. The total UGS area for Sarajevo is 58.5 km², with continuous green spaces present in hilly and mountainous areas of the city, whereas more built-up zones are present in flat areas. The total public UGS per capita is 28.0 m², or 9.8 m² if forest parks are excluded. The results can help in better understanding UGSs in Sarajevo and can serve as a reference for decisionmakers and policymakers.